CHINESE IMMIGRATION TO THE USA ON THE PAGES OF THE MAGAZINE «OTECHESTVENNYE ZAPISKI» (1870S) - Prilutskiy V.V. (Вестник Брянского государственного университета)
The article examines the reflection of Chinese immigration to the United States in the late 1840s – 1870s on the pages of the famous Russian literary magazine «Otechestvennye Zapiski» («Domestic Notes») in the 1870s. In total, they entered America in 1849-1882. About 300 thousand Chinese, but most of them were in the United States temporarily, being labor migrants. Many returned soon to their homeland. Since the 1870s, about 70 thousand people have lived in the country permanently, and this number remained unchanged until the 1940s. Nowadays (due to new waves of migration after 1943-1949 and after 1965), up to 4 million ethnic Chinese and about 1,4 million people of mixed descent with Chinese roots (1,5-1,6% of the population) live in the United States. The periodical «Otechestvennye Zapiski», published intermittently in 1818-1884, was an influential «thick» magazine that had a significant impact on public thought and public opinion of the Russian Empire in the XIXth century. The authors of the articles were divided into two groups. Conservative publicists negatively assessed Chinese immigration, believing that labor migrants are distinguished by their alleged «barbarism» and antisocial lifestyle. Immigrants from China, in their opinion, only knocked down prices in the American labor market. Other journalists (the so-called «liberals») believed that the Chinese would eventually be successfully integrated into the society of a country known for its constitutional guarantees of the protection of rights and freedoms. However, the latter predictions were not destined to come true, since the first restrictions on Chinese labor were introduced as early as the 1870s. Subsequently, the US authorities banned immigration from Asian countries altogether. An influential anti-Chinese political movement has emerged in America.